(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The research problem stemmed from several axes, including weakness in the performance of the plans during the performance, and this weakness is the result of not using broad vision exercises that help players to see the field of play in a comprehensive and rapid manner and the ongoing movements of colleagues and competitors, and the other axis is the lack of interest of many coaches Using wide vision exercises within the training units compared to the physical, skill and planning aspects, and the lack of awareness by the players of the importance of these exercises as their knowledge of physical and skill exercises, in addition to the intellectual controversy by researchers and the book regarding broad vision exercises For the purpose of developing football performance for young players, the researchers intended to apply broad vision exercises on the Khairat Sports Club, drawn randomly (lots) from the Karbala Clubs community, where the club was divided into two groups (control and experimental) for each group (10 players), and the goal was to develop a performance plan. After performing the pretests and applying the exercises prepared by the researchers for a period of 9 weeks and at the time of 3 weekly units, then conducting the post-tests and obtaining the results, the effect of the wide vision exercises in developing the linear performance of the research sample was determined.